TC Chair Highlight: Wen-Mei Hwu and Hyesoon Kim of the Technical Community on Microprogramming and Microarchitecture (TCuARCH). (Computer (00189162), 2022)
IEEE Computer Society (CS) technical communities (TCs) are the foundry from which all our technical conferences are built and run. Our TCs attract all kinds of people in the field who come together to plan events, serve volunteer leadership roles, and help define the features and future of these technical spaces.